Macroscopic yarns of FeCl3-intercalated collapsed carbon nanotubes with high doping and stability. (March 2021) - Madrona, Cristina; Vila, María; Oropeza, Freddy E.; de la Peña O'Shea, Víctor A.; Vilatela, Juan J.
Abstract: Macroscopic arrays of highly-crystalline nanocarbons offer the possibility of modifying the electronic structure of their low dimensional constituents, for example through doping, and studying the resulting collective bulk behaviour. Insertion of electron donors or acceptors between graphitic layers is an attractive method to reversibly increase charge carrier concentration without disruption of the sp2-conjugated system. This work demonstrates FeCl3 intercalation into fibres made up of collapsed (flattened) carbon nanotubes. The bundles of collapsed CNTs, similar to crystallites of graphitic nanoribbons, host elongated layered FeCl3 crystals of hundreds of nm long, much longer than previous reports on graphitic materials and directly observable by transmission electron microscopy and X-ray diffraction. Intercalated CNT fibres remain stable after months of exposure to ambient conditions, partly due to the spontaneous formation of passivating monolayers of FeClO at the crystal edge, preventing both desorption of intercalant and further hydrolysis. Raman spectroscopy shows substantial electron transfer from the CNTs to FeCl3, a well-known acceptor, as observed by G band upshifts as large as 25 cm −1 . After resolving Raman features for the inner and outer layers of the collapsed CNTs, strain and dynamic effect contributions of charge transfer to the Raman upshift could be decoupled, giving a Fermi level downshift of −0.72 eV and a large average free carrier concentration of 5.3·10 13  cm −2 (0.014 electrons per carbon atom) in the intercalated system. Four-probe resistivity measurements show an increase in conductivity by a factor of six upon intercalation. Graphical abstract: Image 1